A facile electrosynthesis approach of Mn-Ni-Co ternary phosphides as binder-free active electrode materials for high-performance electrochemical supercapacitors. (1st June 2021) - Saleh, Amina A.; Amer, Aya; Sayed, Doha M.; Allam, Nageh K.
Highlights: Ternary metallic phosphide-based electrodes have been successfully fabricated. CVD is a very promising tool to ensure homogenous phosphidation of the surface. The 3D networks and porous nanosheets enhanced the capacity performance. The device sustains 1.5 V with exceptional specific capacitance of 176.8 f g −1 at 1 a g −1 . The device delivers specific energy of 55.2 Wh kg −1 at a power density of 749.91 W kg −1 . Abstract: Despite the massive efforts to produce binary metallic phosphides as electrode materials for energy storage purposes, little attempts are devoted to design ternary metallic phosphides, which should perform better than their single and binary counterparts. In this work, we demonstrate the fabrication of 3D flower-like ternary metallic manganese-nickel-cobalt phosphides (MNCPs) with different metal proportions using electrodeposition followed by low-temperature PH3 plasma treatment. Besides the positive synergistic effect of combining the three transition metals, the intriguing architecture with 3D networks and porous nanosheets enhances the capacity performance by facilitating fast electrolyte transport and active sites accessibility for high specific capacity. The best performing electrode reaches an ultra-high capacity of 1690 C g −1 (equivalent to 3380 F g −1 ) in the three-electrode system at a current density of 1 A g −1 . The device combines both MNCP electrode and a bio-derived microporous carbon sheets (MCS) electrode sustains 1.5 V with exceptional specific capacitance of 176.8 F g −1 at 1 A g −1 . The MNCP//MCS device manifests outstanding specific energy of 55.2 Wh kg −1 at a power density of 749.91 W kg −1 . Importantly, the device maintains a high capacitive retention of 96% upon cycling over 8, 000 charge−discharge cycles at 10 A g −1 . This impressive electrochemical performance designates that ternary metallic NiCoMn phosphides are promising candidates for energy storage applications. Graphical abstract: Image, graphical abstract